Perancangan Aplikasi Permintaan dan Pemakaian Bahan Baku di PT. Indofood Divisi Noodle - Rohmat Taufiq; Zaenal Arifin; Nurdiana Handayani; Liesnaningsih Liesnaningsih; Dian Kasoni (Universitas Muhammadiyah Tangerang, 2023)
In this study, it discusses the design and construction of applications for demand and use of raw materials at PT. Indofood CBP Sukses Tbk (Noodle Division). This research is important because the company often loses reports on requests for raw materials, the request process still uses via telephone so it is often forgotten to record and is ineffective, the raw material request process still uses the manual method so it is prone to errors when writing. The methods used during the process of compiling this scientific paper include data collection in the form of observation, interviews and library research. In addition, the system development process uses the SDLC method, the system analysis method uses SWOT and the Black Box Testing method as a turnover test. The conclusion from this raw material usage and demand system research, data storage in this system is already integrated with the database. So as to reduce the potential for loss and damage to data. In addition, reports on goods data can be accessed from 2 hours to 2 minutes. Keywords: Application, information system, Indofood, SDLC, SWOT .